1999
DOI: 10.1139/g99-038
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive heterochromatin DNA polymorphisms in diploid Medicago sativa ssp. falcata

Abstract: A Giemsa C-banding technique was used to study the amount and location of constitutive heterochromatin in diploid (2n = 2x = 16) Medicago sativa ssp. falcata (L.) Arcangeli. Most accessions had the standard C-banding pattern with centromeric bands on all the chromosomes and a prominent heterochromatic band at the nucleolar organizer regions (NOR) of the satellited (SAT) chromosomes. However, we observed in various accessions that constitutive heterochromatic C-bands can exist at the telomeric ends of all the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
1
11
0
5
Order By: Relevance
“…Although C‐banding patterns often show a high degree of polymorphism in cross‐pollinated species (Gill, 1981; Endo and Gill, 1984; Bauchan and Hossain, 1999), all the observed bands were quite consistent in plants of PI 440215 studied here except for the telomeric band on the short arm of chromosome II. This band was absent in 10 of the 17 plants of the accession.…”
Section: Resultssupporting
confidence: 52%
“…Although C‐banding patterns often show a high degree of polymorphism in cross‐pollinated species (Gill, 1981; Endo and Gill, 1984; Bauchan and Hossain, 1999), all the observed bands were quite consistent in plants of PI 440215 studied here except for the telomeric band on the short arm of chromosome II. This band was absent in 10 of the 17 plants of the accession.…”
Section: Resultssupporting
confidence: 52%
“…In most cases, the chromosome pairs could not be distinguished by their C-banding pattern, the exceptions being chromosomes 1 and 4 which showed a distinct heterochromatin distribution clearly visible in metaphases stained with Giemsa and propidium iodide. A C-banded pericentromeric heterochromatin pattern with occasional intercalary and distal bands has also been found in many Leguminosae (Papilionoideae) genera, including Arachis (Cai et al, 1987), Cicer (Tayyar et al, 1994) and Medicago (Bauchan and Hossain, 1999), which have DNA C-values similar to or smaller (Bennett and Leitch, 1995) than C. juncea (1C = 1.23pg; see Gupta, 1976). Conversely, a variable distribution of heterochromatic regions has been observed in the genus Vicia, that has a considerable variation in haploid nuclear DNA content.…”
Section: Discussion Karyotype Analysis and C-banding Patternmentioning
confidence: 96%
“…Satellite DNA, the main constituent of this genomic fraction, usually occurs in the centromeric region of chromosomes (Chaves et al , 2000), but is also frequently found at telomeres (Shore, 2001). The occurrence of CH at interstitial positions is much less common, although large blocks of interstitial CH have been found in the large chromosomes of some insects (John et al , 1985), plants (Bauchan and Hossain, 1999) and some mammals (Santos et al , 2004; Adega et al , 2007; Meles et al , 2008). …”
Section: Introductionmentioning
confidence: 99%